2022
DOI: 10.1021/acs.biomac.2c01150
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Modular Protein Display Efficiency in SpyTag-Implemented Norovirus-like Particles

Abstract: Genetic fusion and chemical conjugation are the most common approaches for displaying a foreign protein on the surface of virus-like particles (VLPs); however, these methods may negatively affect the formation and stability of VLPs. Here, we aimed to develop a modular display platform for protein decoration on norovirus-like particles (NoV-LPs) by combining the NoV-LP scaffold with the SpyTag/SpyCatcher bioconjugation system, as the NoV-LP is an attractive protein nanoparticle to carry foreign proteins for var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The C-termini of noro-VLPs are located in valleys between the surrounding protruding domains, which positions the M2e peptides (equipped with only a short linker in our construct) between noro-VLP protrusions, potentially limiting the access of large proteins. In future studies, this could be potentially circumvented by fusing multiple peptides in succession to a VLP carrier, as described in (Kim et al, 2013;Lee et al, 2018;Lee et al, 2019) or by separating M2e from noro-VP1 Cterminus by an enlengthened linker like the one introduced recently (Boonyakida et al, 2023). Boonyakida et al used the linker to allow more space between noro-VP1 C-terminus and SpyTag, enhancing conjugation rates for SpyCatcher-fused proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The C-termini of noro-VLPs are located in valleys between the surrounding protruding domains, which positions the M2e peptides (equipped with only a short linker in our construct) between noro-VLP protrusions, potentially limiting the access of large proteins. In future studies, this could be potentially circumvented by fusing multiple peptides in succession to a VLP carrier, as described in (Kim et al, 2013;Lee et al, 2018;Lee et al, 2019) or by separating M2e from noro-VP1 Cterminus by an enlengthened linker like the one introduced recently (Boonyakida et al, 2023). Boonyakida et al used the linker to allow more space between noro-VP1 C-terminus and SpyTag, enhancing conjugation rates for SpyCatcher-fused proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Boonyakida et al inserted a linker (EAAAK)n (n = 2,3) between the SpyTag and the VP1 protein to increase surface exposure of the SpyTag on the NoV-LPs. They discovered that the conjugation efficiency of the VP1–SpyTag with the linker (EAAAK)n (n = 2,3) improved from ∼15–35 to ∼50–63% based on the densitometric analysis (Boonyakida et al 2023 ). Cai et al redesigned albumin-fusion cocaine hydrolase CocH1 (TV-1380) to extend its biological half-life.…”
Section: Design and Selection Of Linker Between The Fusion Proteinmentioning
confidence: 99%
“…assembled photothermal reagents AuNP, peptide drugs, and cancer‐cell‐targeting peptides in DNA hydrogels to construct a powerful cancer‐specific peptide drug delivery system. [ 92 ] Herein, the targeted peptide can specifically deliver the nanocomplex to the cancer cells, and after light illumination activated the AuNP, the light‐absorbing thermal conversion effectively deformed the DNA hydrogel, resulting in the release of peptide drugs. The cell viability and Bradford study have confirmed the high efficiency and safety of this photothermal‐triggered mode.…”
Section: Applications Of Functional Dna Hydrogels Based On Nanomaterialsmentioning
confidence: 99%